2022
DOI: 10.3389/fbioe.2022.913900
|View full text |Cite
|
Sign up to set email alerts
|

Primary Repair for Treating Acute Proximal Anterior Cruciate Ligament Tears: A Histological Analysis and Prospective Clinical Trial

Abstract: Reconstruction surgery for acute proximal anterior cruciate ligament (ACL) tears remains controversial. Recently, ACL primary repair has received increasing attention in ACL treatment. This study aimed to explore the histological characteristics of ACL healing in primary repair and compare its therapeutic and prognostic results with the reconstruction of acute proximal ACL tears. Histological experiments using rabbits and a prospective clinical trial were conducted. We established a rabbit model of ACL primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Primary repair promotes cell proliferation in the tendon-bone transitional zone and ligament portions, reduces osteoarthritis-like pathological changes, and maintains blood vessels within the ACL. Histological immunohistochemical research using CD34, the most sensitive endothelial marker of blood vessels, confirmed that the microvessels have a significant effect on tissue healing during the primary repair [18]. Our research performing CD34 immunostaining reported a fine synovial arterial network on the ACL surface from which originated thin vessels for the fibrous tissue of the ligament itself, and penetrating vessels for its femoral attachment and surrounding femoral bony tissue.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Primary repair promotes cell proliferation in the tendon-bone transitional zone and ligament portions, reduces osteoarthritis-like pathological changes, and maintains blood vessels within the ACL. Histological immunohistochemical research using CD34, the most sensitive endothelial marker of blood vessels, confirmed that the microvessels have a significant effect on tissue healing during the primary repair [18]. Our research performing CD34 immunostaining reported a fine synovial arterial network on the ACL surface from which originated thin vessels for the fibrous tissue of the ligament itself, and penetrating vessels for its femoral attachment and surrounding femoral bony tissue.…”
Section: Discussionsupporting
confidence: 62%
“…Restoration of native ACL maintains its structural anatomical characteristics, proprioceptive and biomechanical functions. ACL primary repair is safe less invasive procedure, avoids graft-related complications, and faster rehabilitation is possible [18,19]. Preserved periligamentous synovial sheath should be confirmed before the repair because of the mesenchymal stem cells which are evident in the tissue surrounding the blood vessels [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation